MODIFIKASI TABUNG DAN KARET PADA MESIN PENGUPAS BAWANG MERAH SISTEM HORIZONTAL - Prayogo, Agung Pangestu; Saparin, Saparin; Wijianti, Eka Sari; Setiawan, Yudi (AUSTENIT, 2022)
This research about how to modify a machine that peels onions. The method used is Reverse engineering. This machine was modified because there is a shortage, level of success onion-peeler machine is still low, with value 43.63%, safety level machine is not sufficient, and the diameter of peeler tube hole is too large, so it is not effective and efficient. Modification made for to improve the efficiency of peeling shallots. The modified part is the rubber and the diameter of the peeler hole. Tube-hole size changed from 16mm to 6mm. will use the Shaft On the stripper tube. The shaft works like a holder for a rubber peeler. There are 11 pieces of peeling rubber. The results of the study showed that the peeled onion was 755 grams after 20 minutes. The machine's actual capacity is 37.75 grams per minute, or 2.26 kg per hour. The machine's production efficiency is 75.5%.